Impact of MAPs on improving the socio-economic situation of rural families in Kosovo - Lindita Ibishi; Arben Musliu (Journal of Agriculture and Environment for International Development)
he medicinal and aromatic plants sector is considered a very important sector for the economy of Kosovo since it can provide employment, income, and export growth. Based on this, we assess the impact of the subsidy schemes from the Ministry of Agriculture, Forestry, and Rural Development (MAFRD) using a propensity score matching improving the farmers' gross income. The main purpose of the study was to assess whether subsidy schemes have an impact on the farmer's gross income by using a propensity score matching model to match beneficiaries to non-beneficiaries. Results showed that beneficiaries of subsidy schemes make 3,682.09 Euros more per year than non-beneficiaries (95% confidence interval 2,349.9 Euros to 5,012.90 Euros). Using logistic regression, we found that subsidy schemes, market prices, and reductions of unfair competition are the three most important factors affecting farmers' decisions to collect and cultivate MAPs.